ROLE OF SERICITE IN MODULATING GUT MICROBES AND HAEMATOLOGICAL PROFILES OF SILVER CARP (Journal of Medical & Health Sciences Review, 2025)
Researchers explored sericite's impact on Silver carp's health and growth, conducting a feeding trial with 2.5% and 5% sericite levels. The study examined intestinal tissues and gut microbiota, revealing reduced microorganisms, especially E.coli and Enterobacteriaceae. Sericite may possess antibacterial properties or promote healthier gut microbiota. Hematological parameters improved with sericite inclusion, including increased Hb, Htc, and RBCs, enhancing oxygen-carrying capacity and blood health. Immune responses also strengthened, with elevated WBCs, monocytes, and lymphocytes. These findings suggest sericite's potential benefits in sustainable aquaculture, reducing disease susceptibility and promoting fish well-being. Overall, sericite shows promise for enhancing Silver carp's health and well-being, making it a valuable additive for fish feed and a potential tool for promoting sustainable aquaculture practices.